Epoxy resin prepreg, adhesive film, copper foil substrate and preparation method of prepreg
By conducting esterification and etherification reactions in the presence of ethyl acetate, the molecular weight and distribution of epoxy resin are controlled, and the dielectric properties and heat resistance of epoxy resin-based prepregs are solved, and the comprehensive performance of the material is improved, which is suitable for printed circuit boards in the high-frequency field.
Patent Information
- Application Number
- CN202411838900.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing epoxy resin-based prepregs are difficult to meet the requirements of Dk value ≤4.2 and Df ≤0.015 under high frequency conditions, and the heat resistance and glass transition temperature of the material are insufficient.
By mixing epoxy resin, small molecule anhydride curing agent and accelerator in a certain proportion, and conducting esterification and etherification reactions in the presence of ethyl acetate, the reaction conditions are controlled to obtain an epoxy resin polymer glue solution with a certain molecular weight and a narrow distribution, the crosslinking density of the material is improved, the Dk and Df values are reduced, and the heat resistance and glass transition temperature are improved.
It achieves excellent comprehensive performance of epoxy resin prepreg, suitable for making semi-cured adhesive films and copper foil substrates, and meets the material requirements of printed circuit boards in the high-frequency field.
Smart Images

Figure CN119638957A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printed circuit boards, and in particular to an epoxy resin prepreg, an adhesive film, a copper foil substrate and a method for preparing the prepreg. Background Art
[0002] Epoxy resin-based prepreg is the most important bonding material in the manufacture of copper foil substrates because of its good insulation and processability, as well as good adhesion between reinforcement materials and copper foil. With the rapid development of industries such as 5G communications, data centers, and automotive electronics, the market demand for high-frequency copper foil substrates continues to increase. In order to meet the application performance under high-frequency conditions, new requirements are put forward for the performance of epoxy resin, requiring the prepared copper foil substrate to have a Dk value of ≤4.2 and a Df of ≤0.015 at a frequency of 1GHz. The material is also required to have a high glass transition temperature and heat resistance.
[0003] Epoxy resin and phenolic resin curing system have higher glass transition temperature, but poor dielectric property. In order to improve the dielectric property of epoxy resin, dielectric loss epoxy resin system in the prior art mainly includes phenolic active ester-epoxy resin curing copolymer, cyanate-epoxy resin-styrene maleic anhydride multi-curing copolymer and benzoxazine-phenolic resin-epoxy resin-styrene maleic anhydride multi-curing copolymer. Among them, phenolic active ester-epoxy resin curing copolymer forms ester exchange reaction, material cost is too high, and glass transition temperature is low. Cyanate-epoxy resin-styrene maleic anhydride multi-curing copolymer, material cost is high, and cyanate is easy to produce aryl imine carbonate during curing process, resulting in poor moisture absorption and heat resistance. Benzoxazine-phenolic resin-epoxy resin-styrene maleic anhydride multi-curing copolymer has poor compatibility. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an epoxy resin prepreg, an adhesive film, a copper foil substrate and a method for preparing the prepreg. The epoxy resin prepreg prepared by the present invention meets the requirements of Dk value ≤ 4.2, Df ≤ 0.015, and has good heat resistance and a high Tg value.
[0005] In order to achieve the above object, the present invention adopts the following technical solution: According to one aspect of the present invention, there is provided an epoxy resin prepreg, comprising an epoxy resin polymer glue solution, wherein the epoxy resin polymer glue solution is prepared by: The epoxy resin, the small molecule acid anhydride curing agent and the accelerator are first stirred to obtain a premix; the weight ratio of the epoxy resin, the small molecule acid anhydride curing agent and the accelerator is 100:90-100:1-3; Ethyl acetate is added to the premix, and a second stirring reaction is carried out at 40° C. to 80° C. for 4 h to 24 h, and the molecular weight of the epoxy resin polymer glue is controlled to be 6,000 to 15,000.
[0006] The reaction mechanism of epoxy resin polymer glue preparation is as follows: The anhydride group on the phthalic anhydride reacts with the hydroxyl group on the epoxy resin to form a monoester reaction, and then the anhydride group is opened to form a monoester bond with a monocarboxylic acid; the monocarboxylic acid after the anhydride group is opened and the epoxy group is opened to form an ester bond with a hydroxyl group (hydroxy ester).
[0007]
[0008] The present invention mixes epoxy resin, small molecule acid anhydride curing agent and accelerator in a certain proportion, performs esterification and etherification reaction in the presence of ethyl acetate, controls the reaction conditions to obtain epoxy resin with a certain molecular weight and narrow distribution, and the above preparation process can increase the cross-linking density of the material, reduce the formation of secondary hydroxyl groups, reduce the Dk and Df values of the material, and at the same time has good heat resistance and high Tg value, and has excellent comprehensive performance. It is suitable for making semi-cured adhesive film and copper foil substrate, and can meet the material requirements of printed circuit boards in the high-frequency field.
[0009] The present invention adds ethyl acetate to the premix. On the one hand, the ethyl acetate in the reaction system can control the progress of the esterification and etherification reactions of the epoxy resin, which is beneficial to obtaining the epoxy resin polymer glue with a certain molecular weight and a narrow molecular weight distribution. In the present invention, the selection of reaction conditions is very critical. The reaction temperature selected by the present invention is 40°C to 80°C. If the reaction temperature is too low, the prepolymerization process of the system basically does not occur. If the reaction temperature is too high, the epoxy resin will be solidified in a short time. On the other hand, the addition of ethyl acetate to the reaction system of the present invention can play a viscosity dilution role, which is beneficial to the subsequent glass fiber impregnation process.
[0010] According to a further technical solution, the epoxy equivalent of the epoxy resin is 100 to 200; Preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin and alicyclic epoxy resin; Preferably, the epoxy resin comprises 65% to 75% of bisphenol A epoxy resin and 25% to 35% of alicyclic epoxy resin.
[0011] According to a further technical solution, the first stirring adopts a stirring speed of 300rpm to 600rpm; using a higher stirring speed can be conducive to fully mixing and dispersing the epoxy resin, small molecule acid anhydride curing agent and accelerator, thereby improving the dispersion efficiency. The second stirring adopts a stirring speed of 50rpm to 100rpm. Through the first stirring process, the epoxy resin, small molecule acid anhydride curing agent and accelerator have been fully mixed. After adding ethyl acetate, 50rpm to 100rpm is used, which can achieve uniform mixing of materials on the one hand, and on the other hand, avoid the adverse effect of too fast stirring on the generation of epoxy resin polymer.
[0012] According to a further technical solution, the small molecule acid anhydride curing agent is selected from at least one of tetrahydrophthalic anhydride and methylhexahydrophthalic anhydride.
[0013] According to a further technical solution, the accelerator is selected from at least one of dimethylimidazole, diphenylimidazole, 2-ethyl-4-methylimidazole, and 4-dimethylaminopyridine. The use of the above accelerator can catalyze the reaction of epoxy functional groups and facilitate the cross-linking reaction.
[0014] According to a further technical solution, the ethyl acetate is 30% to 50% by weight of the epoxy resin polymer glue; Preferably, the ethyl acetate accounts for 35% to 45% by weight of the epoxy resin polymer glue.
[0015] According to a further technical solution, the molecular weight of the epoxy resin polymer glue is 6000-13000.
[0016] According to a further technical solution, the prepreg further comprises a filler, and the filler is 20% to 40% by weight of the epoxy resin polymer glue; Preferably, the filler is selected from at least one of an organic filler and an inorganic filler; Preferably, the inorganic filler is selected from at least one of crystalline silica, fused silica, spherical silica, and hollow silica. The organic filler may be selected from one or more of polytetrafluoroethylene powder, polyphenylene sulfide, and polyethersulfone powder. According to a further technical solution, the particle size of the filler is 0.01 μm to 50 μm; Preferably, the particle size of the filler is 0.01 μm to 20 μm; Preferably, the particle size of the filler is 0.01 μm to 10 μm.
[0017] If necessary, the present invention may also contain a flame retardant to provide the resin cured product with flame retardant properties and meet the UL94V-0 requirements. There is no particular limitation on the flame retardant added as needed, and it can be a bromine-containing or halogen-free flame retardant, a halogen flame retardant, a silicon-containing flame retardant, a nitrogen-containing flame retardant, etc., preferably without affecting the dielectric properties. Optional commercial materials such as brominated flame retardants such as BT-93, BT-93W, HP-8010, and HP-3010 of Albemarle; halogen-free flame retardants include SP-100, PX-200, PX-202, FR-700, OP-930, and OP-935. The amount of flame retardant used is determined according to whether the cured product meets the UL94V-0 level requirements, and there is no particular limitation.
[0018] According to another aspect of the present invention, a method for preparing the above-mentioned epoxy resin prepreg is provided, which comprises adding the filler into the epoxy resin polymer glue and mixing them evenly.
[0019] According to another aspect of the present invention, a semi-cured adhesive film is provided. The semi-cured adhesive film is obtained by impregnating the reinforcing material in the above-mentioned epoxy resin prepreg, controlling the adhesive amount to 45% to 55%, and drying to remove the solvent.
[0020] According to another aspect of the present invention, there is provided a copper foil substrate, wherein the copper foil substrate is obtained by laminating the semi-cured adhesive film and copper foil and then performing heat pressing and curing; Preferably, the temperature of the hot pressing curing is 80°C to 250°C, and the curing pressure is 8Kg / cm 2 ~60Kg / cm 2 .
[0021] Compared with the prior art, the invention has the following beneficial effects: the invention obtains epoxy resin with a certain molecular weight and narrow distribution by mixing epoxy resin, small molecule acid anhydride curing agent and accelerator in a certain proportion, and performing esterification and etherification reaction in the presence of ethyl acetate, and controlling the reaction conditions. The above preparation process can increase the cross-linking density of the material, reduce the formation of secondary hydroxyl groups, reduce the Dk and Df values of the material, and at the same time have good heat resistance and high Tg value, and excellent comprehensive performance. It is suitable for making semi-cured adhesive film and copper foil substrate, and can meet the material requirements of printed circuit boards in the high-frequency field. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the infrared spectrum of the epoxy resin prepreg obtained in Example 1; Figure 2 This is the infrared spectrum of the epoxy resin glue obtained in Comparative Example 1. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The raw materials used in the following examples and comparative examples of the present invention are as follows: Bisphenol A epoxy resin (supplier: Taiwan Nan Ya; model: NPEL-128; epoxy equivalent: 187); Phenolic resin (supplier: Taiwan Nan Ya; model: NPEH-710HA65; hydroxyl equivalent: 100); The alicyclic epoxy resin was 3,4-epoxycyclohexylcarboxylate (supplier: Tytel; model: TTA-21; molecular weight: 252.31); Tetrahydrophthalic anhydride (supplier: Puyang Huicheng; model: B1001; molecular weight: 152.16); Methylhexahydrophthalic anhydride (supplier: Puyang Huicheng; model: B1013; molecular weight: 168.19); Accelerator dimethylimidazole (supplier: Shikoku Chemical; model: 2-PI; molecular weight: 82.10); 99% high purity silica (supplier: Jiangsu Lianrui; model: NF-2038A; average particle size: 3μm); Ethyl acetate (supplier: Sigma Aldrich; boiling point: 77 °C); Fiberglass cloth (supplier: Taiwan Nan Ya; model: 2116; treatment agent: I-700W); Reverse copper foil (supplier: Taiwan Nan Ya; model: KSHD; thickness: 18μm); The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0025] Example 1 Put 100g of bisphenol A epoxy resin, 100g of tetrahydrophthalic anhydride, and 2g of accelerator into a glue mixing barrel and stir at 500pm for 15min to mix all the raw materials evenly. Set the temperature to 50℃ and pour in ethyl acetate. Stir at 80rpm for 6 hours until the materials are evenly mixed to form epoxy resin prepreg A (ethyl acetate accounts for 40% of the weight of epoxy resin prepreg A). Introduce epoxy resin prepreg A into a glue basin and evenly coat it on 2116 glass fiber cloth. Control the glue content to 50% and then send it into an oven. Bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0026] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0027] Example 2 Put 70g of bisphenol A epoxy resin, 30g of alicyclic epoxy resin, 100g of tetrahydrophthalic anhydride and 2g of accelerator into a glue mixing barrel and stir at 500rpm for 15min to mix all the raw materials evenly. Set the temperature to 50℃ and pour in ethyl acetate. Stir at 80rpm for 6 hours until the materials are evenly mixed to form epoxy resin prepreg B (ethyl acetate accounts for 40% of the weight of epoxy resin prepreg B). Introduce epoxy resin prepreg B into a glue basin and evenly coat it on 2116 glass fiber cloth. Control the glue content to 50% and then send it into an oven. Bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0028] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0029] Example 3 Put 70g of bisphenol A epoxy resin, 30g of alicyclic epoxy resin, 100g of methyl hexahydrophthalic anhydride, and 2g of accelerator into a glue mixing barrel and stir at 500rpm for 15min to mix all the raw materials evenly. Set the temperature to 50℃ and pour in ethyl acetate. Stir at 80rpm for 6 hours until the materials are evenly mixed to form epoxy resin prepreg C (ethyl acetate accounts for 40% of the weight of epoxy resin prepreg C). Introduce epoxy resin prepreg C into a glue basin and evenly coat it on 2116 glass fiber cloth. Control the glue content to 50% and then send it into an oven. Bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0030] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0031] Example 4 Take 100g of epoxy resin prepreg A (prepared by the same method as in Example 1), add 35g of filler thereto, mix and stir evenly, introduce the epoxy resin prepreg into a glue basin, evenly coat it on 2116 glass fiber cloth and control the glue content to 50%, then send it into an oven and bake it at 170°C for 3min to volatilize the solvent to form a semi-cured glue film.
[0032] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0033] Example 5 Take 100g of epoxy resin prepreg B (prepared by the same method as in Example 2), add 35g of filler thereto, mix and stir evenly, introduce the epoxy resin prepreg into a glue basin, evenly coat it on 2116 glass fiber cloth and control the glue content to 50%, then send it into an oven and bake it at 170°C for 3min to volatilize the solvent to form a semi-cured glue film.
[0034] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0035] Example 6 Take 100g of epoxy resin prepreg C (prepared by the same method as in Example 3), add 35g of filler thereto, mix and stir evenly, introduce the epoxy resin prepreg into a glue basin, evenly coat it on 2116 glass fiber cloth and control the glue content to 50%, then send it into an oven and bake it at 170°C for 3min to volatilize the solvent to form a semi-cured glue film.
[0036] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0037] Comparative Example 1 Put 70g of bisphenol A epoxy resin, 30g of alicyclic epoxy resin, 100g of methyl hexahydrophthalic anhydride, and 2g of accelerator into a glue mixing barrel, stir at 500rpm for 15min to mix the raw materials evenly, and disperse and stir at 80rpm for 6 hours until the materials are mixed evenly. Pour the glue into the glue basin and evenly coat it on the 2116 glass fiber cloth, and control the glue content to 50%, then send it into the oven, and bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0038] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0039] Comparative Example 2 Put 70g of bisphenol A epoxy resin, 30g of alicyclic epoxy resin, 100g of tetrahydrophthalic anhydride and 2g of accelerator into a glue mixing bucket, stir and mix evenly at 500rpm, and disperse and stir at 80rpm for 6 hours until the materials are mixed and stirred evenly. Pour the glue into the glue basin and evenly coat it on the 2116 glass fiber cloth. Control the glue content to 50% and then put it into the oven. Bake it at 170℃ for 3min to volatilize the solvent and form a semi-cured glue film.
[0040] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0041] Comparative Example 3 Put 70g of bisphenol A epoxy resin, 30g of alicyclic epoxy resin, 100g of tetrahydrophthalic anhydride and 2g of accelerator into a glue mixing barrel, stir at 500rpm for 15min to mix the raw materials evenly, set the temperature to 40℃ and stir at 80rpm for 6 hours until the materials are mixed evenly. Pour the glue into the glue basin and evenly coat it on the 2116 glass fiber cloth. Control the glue content to 50% and then put it into the oven. Bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0042] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0043] Comparative Example 4 Put 70g of bisphenol A epoxy resin, 30g of alicyclic epoxy resin, 100g of methyl hexahydrophthalic anhydride, and 2g of accelerator into a glue mixing barrel, stir at 500rpm for 15min to mix the raw materials evenly, set the temperature to 40℃, and stir at 80rpm for 6 hours until the materials are mixed evenly. Pour the glue into the glue basin and evenly coat it on the 2116 glass fiber cloth, control the glue content to 50%, and then put it into the oven, bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0044] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0045] Comparative Example 5 Put 70g of bisphenol A epoxy resin, 30g of alicyclic epoxy resin, 100g of tetrahydrophthalic anhydride and 2g of accelerator into a glue mixing bucket and stir at 500rpm for 15min to mix the raw materials evenly. Disperse and stir at 50℃ and 80rpm for 6 hours until the materials are mixed evenly. After the reaction is completed and cooled to room temperature, pour ethyl acetate into the glue basin and stir to mix evenly. Introduce the glue into the glue basin and evenly coat it on the 2116 glass fiber cloth. Control the glue content to 50% and then send it into the oven to volatilize the solvent to form a semi-cured glue film.
[0046] Take two sheets of semi-cured adhesive film, overlap them with copper, and put them into a hot press for curing. After curing, take samples for testing.
[0047] Comparative Example 6 Put 100g of bisphenol A epoxy resin, 82g of phenolic resin and 2g of accelerator into a glue mixing barrel, stir at 500rpm for 15min to mix all the raw materials evenly, pour ethyl acetate at room temperature and stir at 80rpm for 6 hours until the materials are mixed and stirred evenly to form glue. Pour the glue into the glue basin and evenly coat it on 2116 glass fiber cloth and control the glue content to 50%, then put it into the oven and bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0048] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0049] Comparative Example 7 Put 100g of bisphenol A epoxy resin, 82g of phenolic resin, 61g of filler and 2g of accelerator into a glue mixing barrel, stir at 500rpm for 15min to mix all the raw materials evenly, pour ethyl acetate at room temperature and stir at 80rpm for 6 hours until the materials are mixed and stirred evenly to form glue. Pour the glue into the glue basin and evenly coat it on 2116 glass fiber cloth and control the glue content to 50%, then put it into the oven and bake at 170℃ for 3min to volatilize the solvent to form a semi-cured glue film.
[0050] Take two semi-cured films, put them on top of each other and put them into a hot press. 2 The mixture was cured for 60 min and samples were taken for testing after curing.
[0051] The epoxy resin prepreg in Example 1 and the epoxy resin glue in Comparative Example 1 were subjected to infrared spectroscopy detection. Figure 1 and Figure 2 It can be seen that the epoxy resin premix prepared in Example 1 has 1720 ester bonds after the curing reaction, and the comparative example 1 has unreacted C=O in 1860 anhydride and C=O in 1780 anhydride, indicating that the epoxy resin produced a prepolymerization reaction under the conditions of Example 1, while the prepolymerization reaction did not occur under the conditions of comparative example 1.
[0052] The epoxy resin prepreg / semi-cured adhesive film / copper foil substrate prepared in the above examples and comparative examples were tested, wherein (1) to (4) were tested using a copper foil substrate, (5) was tested using an epoxy resin prepreg, and (6) was tested using a semi-cured adhesive film. The specific test methods are as follows: (1) The DSC-Tg test is carried out in accordance with the method specified in IPC-TM650 2.4.25C; (2) The test of T-288 (containing copper) is carried out in accordance with the method specified in IPC-TM650 2.4.24.1; (3) The DK@1GHz test is performed in accordance with the method specified in IPC-TM-650 2.5.5.15; (4) The Df@1GHz test is performed in accordance with the method specified in IPC-TM-650 2.5.5.15; (5) The GPC degree of polymerization (molecular weight) was tested using a gel permeation chromatograph, brand: Waters, with a mobile phase of THF at a concentration of 0.275%; (6) The test method and conditions for tackiness are as follows: at room temperature of 23°C / RH60%, two semi-cured adhesive films are bonded together and then separated. If there is no debonding, it is judged as non-sticky. If there is debonding after separation, it is judged as sticky / very sticky. The performance test results of the samples of Examples 1 to 6 are shown in Table 1, and the performance test results of the samples of Comparative Examples 1 to 7 are shown in Table 2 below: Table 1: Performance test results of samples of Examples 1 to 6
[0053] Table 2: Performance test results of samples of comparative examples 1 to 7
[0054] Combining Example 1 and Example 2, the results show that the selection of alicyclic epoxy resin and bisphenol A epoxy resin compound can increase the Tg value of the epoxy resin prepreg, and reduce Dk and Df. The comprehensive performance of Example 2 is better than that of Example 1.
[0055] Combining Examples 1, 2, 4 and 5, the results show that the Dk of the prepared epoxy resin prepreg is increased by the influence of the filler. While meeting the Dk requirement, the Df decreases after adding the filler, and the Tg value increases.
[0056] Combining Example 3 with Example 6, the results show that using methyl hexahydrophthalic anhydride as a curing agent can also achieve similar effects, but the Tg value is slightly lower than that of the epoxy resin prepreg prepared using tetrahydrophthalic anhydride curing agent.
[0057] Combining Examples 2 to 3 and Comparative Examples 1 to 2, the results show that in the absence of a prepolymerization reaction, the semi-cured adhesive films of Comparative Examples 1 to 2 become very sticky, and their Tg and T-288 are significantly reduced, and the dielectric properties are also poor, indicating that the methods of Examples 2 to 3 of the present application can significantly improve the various properties of the samples by first preparing epoxy resin prepregs.
[0058] Combining Examples 2 to 3 and Comparative Examples 3 to 4, the results show that when ethyl acetate is not added as a solvent and the reaction temperature is low, the prepolymerization reaction is insufficient, the GPC polymerization degree of the samples in Comparative Examples 3 to 4 is low, the semi-cured film still becomes sticky, Tg and T-288 are significantly reduced, and the dielectric properties are also poor.
[0059] Combining Example 2 and Comparative Example 5, the results show that when ethyl acetate is not added during the prepolymerization process, the semi-cured film of Comparative Example 5 becomes sticky, the GPC degree of polymerization molecular weight distribution of the sample is relatively wide, Tg and T-288 are significantly reduced, and the dielectric properties are also poor.
[0060] Combining Examples 1 to 6 with Comparative Examples 6 to 7, the results show that the epoxy resin prepregs prepared in Examples 2, 3, 5 and 6 of the present invention can achieve an effect equivalent to the Tg value of the glue in Comparative Examples 6 to 7, and the T-288, Df, and Dk values of the epoxy resin prepregs prepared in Examples 1 to 6 are significantly better than those in Comparative Examples 6 to 7.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and not to limit it. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present application can still be modified or some technical features can be replaced by equivalents, which should all be included in the scope of the technical solution requested for protection in this application.
Claims
1. An epoxy resin prepreg, characterized in that: The invention comprises epoxy resin polymer glue, and the preparation method of the epoxy resin polymer glue is as follows: The epoxy resin, the small molecule acid anhydride curing agent and the accelerator are first stirred to obtain a premix; the weight ratio of the epoxy resin, the small molecule acid anhydride curing agent and the accelerator is 100:90-100:1-3; Ethyl acetate is added to the premix, and a second stirring reaction is carried out at 40° C. to 80° C. for 4 h to 24 h, and the molecular weight of the epoxy resin polymer glue is controlled to be 6,000 to 15,000.
2. An epoxy resin prepreg according to claim 1, characterized in that: The epoxy equivalent of the epoxy resin is 100 to 200; Preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin and alicyclic epoxy resin; Preferably, the epoxy resin comprises 65% to 75% of bisphenol A epoxy resin and 25% to 35% of alicyclic epoxy resin.
3. An epoxy resin prepreg according to claim 1, characterized in that: The first stirring adopts a stirring speed of 300 rpm to 600 rpm; The second stirring adopts a stirring speed of 50 rpm to 100 rpm.
4. The epoxy resin prepreg according to claim 1, characterized in that: The small molecule acid anhydride curing agent is selected from at least one of tetrahydrophthalic anhydride and methylhexahydrophthalic anhydride; And / or the accelerator is selected from at least one of dimethylimidazole, diphenylimidazole, 2-ethyl-4-methylimidazole and 4-dimethylaminopyridine.
5. The epoxy resin prepreg according to claim 1, characterized in that: The ethyl acetate is 30% to 50% by weight of the epoxy resin polymer glue; Preferably, the ethyl acetate accounts for 35% to 45% by weight of the epoxy resin polymer glue.
6. The epoxy resin prepreg according to claim 1, characterized in that: The molecular weight of the epoxy resin polymer glue is 6000-13000.
7. The epoxy resin prepreg according to claim 1, characterized in that: The prepreg further comprises a filler, wherein the filler is 20% to 40% by weight of the epoxy resin polymer glue; Preferably, the filler is selected from at least one of an organic filler and an inorganic filler; Preferably, the inorganic filler is selected from at least one of crystalline silica, fused silica, spherical silica, and hollow silica; Preferably, the particle size of the filler is 0.01 μm to 50 μm; Preferably, the particle size of the filler is 0.01 μm to 20 μm; Preferably, the particle size of the filler is 0.01 μm to 10 μm.
8. The method for preparing an epoxy resin prepreg according to claim 7, characterized in that: The filler is added into the epoxy resin polymer glue solution and mixed evenly.
9. A semi-cured adhesive film, characterized in that: The semi-cured adhesive film is obtained by impregnating the reinforcing material in the epoxy resin prepreg described in claims 1 to 7, controlling the adhesive amount to 45% to 55%, and drying to remove the solvent.
10. A copper foil substrate, characterized in that: The copper foil substrate is obtained by laminating the semi-cured adhesive film according to claim 9 with copper foil and then performing heat pressing and curing; Preferably, the temperature of the hot pressing curing is 80°C to 250°C, and the curing pressure is 8Kg / cm 2 ~60Kg / cm 2 .
Citation Information
Patent Citations
Anhydride type epoxy resin curing formula
CN106008924A
Environment-friendly copper-clad plate preparing method
CN106183237A
Thermosetting resin composition, and prepreg, laminate and metal foil-clad laminate using same
CN109851997A
Method for preparing epoxy glass cloth insulating cylinder
CN112143006A
Insulating adhesive film material as well as preparation method and application thereof
CN112724867A